Business Strategy Planning Case Study: PT Sera Food Indonesia - Dwi Ningsih (Publikasi Indonesia, 2024)
This study aims to look at the position of PT Serafood Indonesia in the rotation of the food business, especially meat processed ingredients. By knowing the position of the company, it will get the right position for stakeholders to develop the company's business. This type of research is a qualitative descriptive. To collect data in this study used field observations and interviews. Resource persons in this study were 7 people consisting of the owner, general manager and managers as decision makers at PT Serafood Indonesia. This study uses a SWOT analysis from Pearce and Robinson. Data analysis used is the IFAS matrix analysis technique (Internal Factor Analysis Summary) and the EFAS matrix (External Factor Analysis Summary) and SWOT matrix analysis (Strengths, Weaknesses, Opportunities, Threats). The EFAS results get a value of 0.054 and IFAS is 0.356. In the SWOT matrix diagram, it shows that the condition of the institution is in quadrant 1. The results of the research analysis can be concluded that PT Serafood Indonesia has opportunities and strengths as well as good abilities in dealing with threats and weaknesses. To win the competition in the processed food industry, the right strategy planning for PT Serafood Indonesia is to support an aggressive growth policy with a choice of strategies are market penetration, market development and product development.